2006
DOI: 10.1080/09553000600632261
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially transcribed genes in human lymphoblastoid cells irradiated with 0.5 Gy of γ-ray and the involvement of low dose radiation inducibleCHD6gene in cell proliferation and radiosensitivity

Abstract: This study has identified a set of genes responsive to 0.5 Gy of gamma-rays. CDH6 gene can be specifically up-regulated by low dose irradiation, and its inducible expression could be involved in a low dose hypersensitive response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 26 publications
1
25
1
Order By: Relevance
“…Although this is the first report that provides evidence for the role of a CHD family member in DNA repair, an earlier study has shown the induction of CHD6 in response to low dose gamma-ray irradiation in various cell lines. Interestingly, silencing of CHD6 also increased the resistance of A549 cells to low dose radiation, whereas radiosensitivity was unchanged in response to doses larger than 4 Gy, implicating a mechanistic role of CHD6 in cellular responses to low dose radiation [Wang et al, 2006]. In addition, the CHD4 protein has been shown to interact with the ataxia telangiectasia mutated and Rad3-related protein (ATR) that is known to be involved in various DNA damage response pathways [Schmidt and Schreiber, 1999;Abraham, 2001;Durocher and Jackson, 2001].…”
Section: Discussionmentioning
confidence: 97%
“…Although this is the first report that provides evidence for the role of a CHD family member in DNA repair, an earlier study has shown the induction of CHD6 in response to low dose gamma-ray irradiation in various cell lines. Interestingly, silencing of CHD6 also increased the resistance of A549 cells to low dose radiation, whereas radiosensitivity was unchanged in response to doses larger than 4 Gy, implicating a mechanistic role of CHD6 in cellular responses to low dose radiation [Wang et al, 2006]. In addition, the CHD4 protein has been shown to interact with the ataxia telangiectasia mutated and Rad3-related protein (ATR) that is known to be involved in various DNA damage response pathways [Schmidt and Schreiber, 1999;Abraham, 2001;Durocher and Jackson, 2001].…”
Section: Discussionmentioning
confidence: 97%
“…There is an increasing concern about the hazardous effects caused by a 'very-low' (<0.2 Gy) dose of IR. While there are several large-scale gene expression studies for the differential effect between the high (>2 Gy) and low (<2 Gy) dose of IR (24)(25)(26)(27), there are fewer studies concerning the low and 'very-low' dose effects on gene expression. Moreover, most of the low or 'very-low' dose-based IR studies were performed at a single fixed time point following exposure without any consideration of the time-dependent experimental effects.…”
Section: Introductionmentioning
confidence: 99%
“…We focused our study on 24 radiation responsive ERP29 ERP29 candidate genes because these genes were previously documented to be connected with functions intimately linked to cancer (Table 2). [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Among the 24 genes, observations from previous studies noted post CT changes within 1 hour after radiation in 11 genes with 4 of them (ATM, ERP29, TP53, CDKN2A) showing post CT changes from very low radiation doses, as low as 0.1 Gy. Owing to their higher radiosensitivity, children are expected to react more sensitively than adults to the CT-induced radiation insult, and therefore, we included all 24 genes in our study, although some observations were reported longer than 1 hr post CT or after IR doses higher than those used in our study.…”
Section: Discussionmentioning
confidence: 99%